Identification of autoimmune markers in pulmonary tuberculosis - Starshinova, Anna; Malkova, Anna; Zinchenko, Yulia; Kudryavtsev, Igor; Serebriakova, Maria; Akisheva, Tatiana; Lapin, Sergey; Mazing, Aleksandra; Kudlay, Dmitry; Glushkova, Anzhela; Yablonskiy, Piotr; Shoenfeld, Yehuda (Frontiers in Immunology, 2023)
Introduction. Pathogenesis of many autoimmune diseases is mainly promoted by poorly regulated and/or wrong targeted immune responses to pathogens including M. tuberculosis. Autoimmunity is one of the processes characteristics of tuberculosis (Tbc). The aim was to determine the autoimmune clinical and immunological features in patients with pulmonary Tbc. Materials and methods. A prospective comparative study was performed in 2017 – 2019 with the inclusion of 46 patients with Tbc. The trigger factors and clinical manifestations, autoantibodies, peripheral blood B cell subsets were stained with fluorochrome-conjugated monoclonal antibodies. The control group comprised of 40 matched for age and sex healthy volunteers with no chronic diseases, contacts with tuberculosis and changes in their laboratory parameters. A statistical analysis was done with GraphPad Prism 6, Statistica 10 (Statsoft) and MedCalc – version 18.2.1 values. Results. There were no significant ASIA triggers in Tbc patients and control group. 21.1% of Tbc patients had a high level of rheumatoid factor and in 47.4% complement system factor C3 was high; anti-MCV was detected in 60.7% of Tbc patients. Relative and absolute frequencies of “naïve” Bm1 cells and eBm5 were significantly decreased and activated pre-germinal-center Bm2’ cells were significantly increased in Tbc patients. The CD24++CD38++ B cells were increased in Tbc vs. controls (10.25% vs. 5.42%), p < 0.001, and 19 cell/1μL (10; 290 vs. 11 cell/1μL (6; 20), p = 0.029, respectively). The frequency of CXCR3+CCR4– Tfh1 cells were significantly lower in Tbc vs. controls (26.52% vs. 31.00%, p = 0.004), while CXCR3–CCR4+ Tfh2 cells were increased in Tbc (20.31% vs. controls (16.56%, p = 0.030). The absolute numbers of Tfh1 cells were decreased in the Tbc vs. control (24 cell/1μL vs. 37 cell/1μL p = 0.005). Conclusion. The results of our study showed that the detection of rheumatoid factor, components of complement system and anti-MCV in complex with alterations in B cell and follicular Th cell subsets may indicate a presence of autoimmunity in the pathogenesis of tuberculosis, but are not specific. The indicators of autoimmune-related provide new opportunities in pulmonary tuberculosis treatment.